2021
DOI: 10.3390/jof7080605
|View full text |Cite
|
Sign up to set email alerts
|

Testing Practices for Fungal Respiratory Infections and SARS-CoV-2 among Infectious Disease Specialists, United States

Abstract: In an online poll, 174 infectious disease physicians reported that testing frequencies for coccidioidomycosis, histoplasmosis, blastomycosis, and cryptococcosis were similar before and during the COVID-19 pandemic, indicating that these physicians remain alert for these fungal infections and were generally not concerned about the possibility of under-detection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
0
3
0
2
Order By: Relevance
“…If the COVID-19 pandemic had not occurred, surely this series would show more than 500 cases. Unlike other fungal respiratory infections, no relationship between COVID-19 and PCM was documented [14,15].…”
Section: Discussionmentioning
confidence: 96%
“…If the COVID-19 pandemic had not occurred, surely this series would show more than 500 cases. Unlike other fungal respiratory infections, no relationship between COVID-19 and PCM was documented [14,15].…”
Section: Discussionmentioning
confidence: 96%
“…Another way to refer to the situation would be the "anchoring bias," defined as relying too heavily on a specific piece of information in order to make a decision, thereby creating situations of delay in treatment for the correct diagnosis experienced [111]. In general, it has been reported that COVID-19 did not impact testing frequencies for CM, histoplasmosis, blastomycosis, and cryptococcosis respiratory infections among a group of 174 infectious disease specialists; however, this observation should be taken with caution due to significant evidence of the diseases being historically underdiagnosed [112]. Furthermore, a lack of bronchoscopies and necropsies, occurring due to aerosolization risk of COVID-19, may be to blame for lack of fungal infection cases being reported [113].…”
Section: And Covid-19mentioning
confidence: 98%
“…infection. A survey of infectious disease physicians indicated that testing practices did not change because of COVID-19, though primary care doctors were not among the respondents to this survey [ 97 ]. It is also unknown whether health-seeking behavior or access to healthcare during the pandemic affected coccidioidomycosis case counts.…”
Section: Epidemiologymentioning
confidence: 99%